Effect of chemical composition and Co-core size on the magnetic and magneto-transport properties of CoyAg100−y core–shell nanocrystallites. Issue 18 (11th December 2016) - Kamal, S. S. Kalyan; Vimala, J.; Sahoo, P. K.; Ghosal, P.; Raja, M. Manivel; Durai, L.; Ram, S.
ABSTRACT: This paper describes the applicability of a modified polyol process in conjunction with a transmetallation reaction in synthesis of Co y Ag100− y nanocrystallites of a core–shell structure. The substitution Co → Ag is varied as 20 ≤ y ≤ 95 by tuning the microstructure with functional magnetic and giant magneto resistance properties. The existence of core–shell structures was confirmed through transmission electron microscope and the size of Co-core increased from 8 to 50 nm with decrease in Ag-content of the sample. The magnetic behaviour of the sample changed from a pseudo-superparamagnetic nature to ferromagnetic with increase in Co-core size. Normalised saturation magnetisation values increased from 89.5 to 128.6 emu/g with increase in size of Co-core; however, none of the ferromagnetic samples exhibited any magneto resistance (MR). A value of 2.0% MR was observed in case of Co20.6 Ag79.4 which increased to a maximum of 3.6% MR for Co36.6 Ag63.4 sample when measured at 5 K.